Wheat Stem Rust Back in Europe: Diversity, Prevalence and Impact on Host Resistance - Patpour, Mehran; Hovmøller, Mogens S.; Rodriguez-Algaba, Julian; Randazzo, Biagio; Villegas, Dolors; Shamanin, Vladimir P.; Berlin, Anna; Flath, Kerstin; Czembor, Pawel; Hanzalova, Alena; Sliková, Svetlana; Skolotneva, Ekaterina S.; et al. (Frontiers in Plant Science, 2022)
The objective of this study was to investigate the re-emergence of a previously important crop pathogen in Europe, Puccinia graminis f.sp. tritici, causing wheat stem rust. The pathogenhas been insignificant in Europe for more than 60 years, but since 2016 causing epidemics on both durum wheat and bread wheat in local areas in southern Europe, and additional outbreaks in Central- and West Europe. The prevalence of three distinct genotypes/races in many areas, Clade III-B (TTRTF), Clade IV-B (TKTTF) and Clade IV-F (TKKTF), suggested clonal reproduction and additional evolution by mutation within these. None of these genetic groups and races, which likely originated from exotic incursions, were detected in Europe prior to 2016. A fourth genetic group, Clade VIII, detected in Germany (2013), was observed in several years in Central- and East Europe. Tests of representative European wheat varieties with prevalent races revealed high level of susceptibility. In contrast, high diversity with respect to virulence and Simple Sequence Repeat (SSR) markes were detected in local populations on cereals and grasses in proximity to the alternate host, Berberis species, in Spain and Sweden. A geographical distant population from Omsk and Novosibirsk in western Siberia also revealed high genetic diversity, but clearly different from current European populations. The presence of Sr31-virulence in multiple and highly diverse races in local populations in Spain and Siberia stress that virulence may emerge independently when large geographical areas and time spans are considered and that Sr31-virulence is not unique to Ug99. All isolates of the Spanish populations, collected from wheat, rye and grass species, were succesfully recovered on wheat, which underline the plasticity of host barriers within P. graminis. The study demonstrated successful alignment of results from different laboratories based on SNP and SSR genotyping, respectively, as well as race phenotyping, which allowed us to line up with previous European and international studies of wheat stem rust. Our results suggest that Berberis species may return as an important component in the epidemiology of wheat stem rust in Europe. New breeding efforts to increase stem rust resistance in European wheat germplasm is strongly recommended.